Organizing bell hooks’ frameworks for interrogating representations - Biana, Hazel T. (2022)
Access online through this link: https://www.plarideljournal.org/article/organizing-bell-hooks-frameworks-for-interrogating-representations
Keywords: Social criticism; Feminist theory; Critical discourse analysis